The Role of Iron in Bacterial Pathogenesis - Susu M. Zughaier (Frontiers Research Topics, 2018)
The collection of articles published in this eBook represent different facets of the interactions between pathogens and their host concerning the battle for iron. Pathogens have developed different strategies to acquire iron from their host. These include the production of siderophores, heme acquisition and ferrous iron uptake.